2009
DOI: 10.1017/s0317167100006557
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Discectomy: A National Survey of Neurosurgeons and Literature Review

Abstract: The prevalence of symptomatic lumbar disc herniation is approximately 2% in the adult population 1 . When conservative therapy (e.g., analgesia, physiotherapy) does not provide optimum symptom relief, lumbar discectomy is regarded as the treatment of choice with a success rate of 74 to 98% 2 . However, the adjuvant pre-, intra-and post-operative management principles vary among practising neurosurgeons, such as the use of various diagnostic imaging techniques, epidural steroids, ABSTRACT: Background: To ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Four more trials have been published since [2-5]. In addition a survey of 112 Canadian neurosurgeons in 2009 showed that 61% of participants do not use epidural steroids in lumbar discectomy [6]. This would indicate that the clinical use of intraoperative steroids in lumbar discectomy is still a matter of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Four more trials have been published since [2-5]. In addition a survey of 112 Canadian neurosurgeons in 2009 showed that 61% of participants do not use epidural steroids in lumbar discectomy [6]. This would indicate that the clinical use of intraoperative steroids in lumbar discectomy is still a matter of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…In a Canadian study published in 2009, 49% of surgeons routinely used epidural steroids after surgery. 6 With this widespread but nonstandardized use of epidural steroids after lumbar discectomy, a better understanding of their associated risk is warranted.…”
mentioning
confidence: 99%
“…Generally, unilateral transflaval discectomy with loupes or microscopic magnification are both considered as microdiscectomy and internationally defined as the standard method of treatment of lumbar disc-related sciatica. This is supported by a Canadian and Dutch survey held among spine surgeons showing that the majority of the respondents performed unilateral transflaval microdiscectomy as the standard surgical procedure in their practice [6, 8]. …”
Section: Surgical Techniquesmentioning
confidence: 88%